The Influence of Financial Literacy, Financial Attitude, Locus of Control, and Government Assistance on the Financial Behavior of Aid-Recipient Small and Medium Enterprises (SMEs) in the City of Langsa - Merci Dewi Sinta; Muhammad Fuad; Meutia Dewi (Pasundan Social Science Development, 2023)
This research aims to determine the influence of financial literacy, financial attitudes, locus of control and government assistance on financial behavior in MSMEs receiving assistance in Langsa City. The sample in this study amounted to 374 people. The data analysis method uses multiple linear regression analysis, t test, F test, and coefficient of determination test. The regression equation in this research is Y = 4.116 + 0.311X1 + 0.120X2 + 0.060X3 + 0.201X4. A constant of 4.116 shows the value of financial behavior in MSMEs if financial literacy, financial attitude, locus of control and government assistance have a fixed value. The regression coefficients of financial literacy, financial attitudes, locus of control and government assistance show a positive influence on the financial behavior of MSMEs. Financial literacy, financial attitudes, locus of control and government assistance partially have a significant effect on the financial behavior of MSMEs receiving assistance in Langsa City, where from the t test the t sig value is obtained. each variable is 0.00 < 0.05. Financial literacy, financial attitudes, locus of control and government assistance simultaneously have a significant effect on the financial behavior of MSMEs receiving assistance in Langsa City, where from the F test the F sig value is obtained. equal to 0.00 < 0.05. From the analysis of the coefficient of determination it is known that the variables financial literacy, financial attitude, locus of control and government assistance influence the financial behavior of MSMEs receiving assistance in Langsa City by 52.4%, while the remaining 47.6% is influenced by other variables outside this research model.